Hydrographic and Tidal Information for Deep Draught Ships in a Tidal Estuary - White, J. C.E. (The International Hydrographic Review, 2015)
The principal oil refineries in the Port of London are situated at Thameshaven and Coryton, over 50 miles from the true entrance to the port at Long Sand Head. Here deep draught tankers first enter areas where charted depths are less than their draught and so require the tide to give sufficient water to navigate. This 50 mile passage is through a complex estuary, where drying sandbanks alternate with deeps; and where two tidal systems (that from the North Sea and that from the Straits of Dover) meet and interact with resultant instability of the sea bed in certain areas; some 12 miles of this passage are dredged. To bring into the Port ships drawing up to 48 feet (100 000 ton tankers fully laden and 200 000 ton tankers part laden) with an underkeel clearance of only 3 - 4 feet requires great skill on the part of the Master and Pilot and this skill must have a sound basis of up-to-date data. They must have accurate hydrographic surveys and actual tidal heights, as well as comprehensive tidal predictions to enable them to plan and execute the passage with safety. This paper discusses the hydrographic surveys required for this purpose in terms of accuracy of measured depth, tidal reduction of soundings, and accuracy of position fixing and how this is applied in the Port of London. It also describes the tidal predictions used, and how, by means of radio-linked tide gauges and the port’s communication system actual tidal information is passed to the ships. The means of interpreting this information co-tidally along the 50 mile passage is also described. The paper then briefly discusses future requirements in this field.